CCL20, γδ T cells, and IL-22 in corneal epithelial healing - Li, Zhijie (Federation of American Societies for Experimental Biology, 2011)
After corneal epithelial abrasion, leukocytes and platelets rapidly enter the corneal stroma, and CCR6(+) IL-17(+) γδ T cells migrate into the epithelium. γδ T-cell-deficient (TCRδ(−/−)) mice have significantly reduced inflammation and epithelial wound healing. Epithelial CCL20 mRNA increased 19-fold at 3 h, and protein increased ∼16-fold at 6 h after injury. Systemic or topical treatment of wild-type C57BL/6 mice with anti-CCL20 reduced γδ T-cell accumulation in the cornea by >50% with a concomitant decrease in epithelial healing and stromal inflammation. In addition to CCR6 and IL-17, corneal γδ T cells stained positively for RORγt, IL-23R, and IL-22. Anti-IL-22 reduced peak cell division of the healing epithelium by 52%. Treatment of TCRδ(−/−) mice with rIL-22 significantly promoted wound closure, with peak epithelial cell division increased >3-fold. In addition, rIL-22 restored neutrophil and platelet influx in the TCRδ(−/−) mice to wild-type levels and increased CXCL1 production by wounded corneal explants >2-fold. These results indicate that an important aspect of the healing response to corneal epithelial abrasion includes CCL20-dependent influx of CCR6(+) IL-17(+) IL-22(+) γδ T cells and that IL-22 contributes to the inflammatory response and promotes epithelial healing.—Li, Z., Burns, A. R., Byeseda Miller, S., Smith, C. W. CCL20, γδ T cells, and IL-22 in corneal epithelial healing.